Design and Fabrication of Remote Welding Equipment in a Hot-Cell - Soosung Kim; Kihwan Kim; Jungwon Lee; Jinhyun Koh (Science and Technology of Nuclear Installations)
The remote welding equipment for nuclear fuel bundle fabrication in a hot-cell was designed and developed. To achieve this, a preliminary investigation of hands-on fuel fabrication outside a hot-cell was conducted with a consideration of the constraints caused by the welding in a hot-cell. Some basic experiments were also carried out to improve the end-plate welding process for nuclear fuel bundle fabrication. The resistance welding equipment using end-plate welding was also improved. It was found that the remote resistance welding was more suitable for joining an end-plate to end caps in a hot-cell. This paper presents an outline of the developed welding equipment for nuclear fuel bundle fabrication and reviews a conceptual design of remote welding equipment using a master-slave manipulator. Furthermore, the mechanical considerations and a mock-up simulation test were described. Finally, its performance test results were presented for a mock-up of the remote resistance welding equipment for nuclear fuel bundle fabrication.